Analysis of data on levels of public exposure to natural sources of radiation in the Ivanovo region - T. A. Kormanovskaya; O. A. Daricheva; P. A. Kolesnik; D. V. Kononenko (Радиационная гигиена)
The paper presents the results of analysis of the Ivanovo Regional databank of radiation doses to the pub-lic from exposure to natural and technologically enhanced radiation background for 2008–2022. Despite the fact that the average individual annual effective dose of public exposure due to natural sources of radiation in the Ivanovo region calculated for the whole 15-year period (4.63 mSv/year) does not qualify as increased (i.e.  does  not  exceed  the  level  of  5  mSv/year),  in  some  years  of  the  period  under  review  the  average  dose repeatedly exceeded this level, reaching 7.50 mSv/year. The analysis of the structure of the doses of public exposure due to natural sources of radiation in the Ivanovo region showed that the contribution of the dose from  internal  exposure  to  radon,  thoron  and  progenies  according  to  measurement  results  from  2008–2022 ranged from 65.98 to 81.47%. The paper provides examples of buildings of different types in settlements of the Ivanovo region, in which the indoor radon isotopes equilibrium equivalent concentrations are more than 1.5 times higher than the established action level for existing dwellings and public buildings (200 Bq/m3). Despite the  significant  amount  of  measurement  data  in  the  Regional  databank,  it  is  necessary  to  obtain  additional information on the indoor radon levels in existing wooden and other low-rise dwellings and public buildings in the most radon-prone areas of the region. For this purpose, a radon survey is planned for 2024-2026 in the cities  of  Ivanovo  and  Kohma,  Privolzhsky,  Gavrilovo-Posadsky,  Teykovsky  and  Zavolzhsky  districts  of  the Ivanovo  region  within  the  framework  of  a  joint  project  of  Saint-Petersburg  Research  Institute  of  Radiation Hygiene after Professor P.V. Ramzaev, the Directorate of the Federal Service for Surveillance on Consumer Rights Protection and Human Wellbeing in the Ivanovo region, and the Center of Hygiene and Epidemiology in the Ivanovo region.